2019
DOI: 10.1097/lgt.0000000000000476
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of Women Self-Sampling versus Clinician-Collected Samples for HPV DNA Testing: A Systematic Review

Abstract: Objectives Female self-sampling for human papillomavirus (HPV) DNA testing is an alternative screening method that can potentially increase cervical cancer screening coverage. This review addresses the acceptability of HPV DNA testing using self-sampling compared with conventional clinician-collected sampling. Barriers to and others factors associated with acceptability of either method were also examined. Methods The following electronic resources were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 31 publications
5
36
0
1
Order By: Relevance
“…A preference for HPV self-testing over Pap testing emerged as a primary theme, with more participants preferring the HPV self-test in over 90% of screening modality studies. This overwhelming preference for self-testing over Pap testing is consistent with findings in prior systematic reviews of self-testing acceptability, which all found that participants in the majority of included studies preferred self-testing (22)(23)(24). The consistency of these results, viewed in concert with other reviews, has important implications for the incorporation of HPV self-testing into primary screening practice.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…A preference for HPV self-testing over Pap testing emerged as a primary theme, with more participants preferring the HPV self-test in over 90% of screening modality studies. This overwhelming preference for self-testing over Pap testing is consistent with findings in prior systematic reviews of self-testing acceptability, which all found that participants in the majority of included studies preferred self-testing (22)(23)(24). The consistency of these results, viewed in concert with other reviews, has important implications for the incorporation of HPV self-testing into primary screening practice.…”
Section: Discussionsupporting
confidence: 84%
“…Huynh and colleagues conducted a systematic review of articles published through October 2008 about individual perceptions of HPV self-testing (22). In addition, two studies have systematically reviewed self-sampling acceptability (23,24). While these reviews found self-testing to be generally well received by patients, none have specifically reviewed preferences across the full range of approved screening delivery options or focused on medically underserved populations.…”
Section: Introductionmentioning
confidence: 99%
“…At both study sites, women showed the same attitude regarding self-collection versus clinican collection samples for HPV DNA testing. The high rate of willingness to perform self-collection was not influenced by sociodemographic factors or any other factor studied as observed in previous studies [41,42]. This underscores the strong scientific basis for implementing self-collection in CC screening, thereby enabling women from communities and rural settings where CC screening programmes are presently not available to participate.…”
Section: Plos Onesupporting
confidence: 67%
“…Mao and colleagues (2017) reported that women who prefer a clinician-collection want to have a one-on-one consultation with a clinician, so that they can address other issues they may have [44]. Other factors that women are raising include adequacy of the specimen and lack of confidence to perform self-collection correctly [42,45]. Therefore, our findings suggest that women should be given an opportunity to choose which method they prefer for specimen collection, when participating in the CC screening programme.…”
Section: Plos Onementioning
confidence: 99%
“…In a recent meta-analysis, the sensitivities and specificities of patient self-sampling compared with those collected by physicians for detecting HPV were comparable (74% and 88% vs 81% and 90%, respectively) 21 22. Furthermore, many studies implemented in various international regions show that the majority of women screened by the self-swab method are willing and able to perform the test 23 24…”
Section: Introductionmentioning
confidence: 99%